Axial turbine wheel design for mini trubojet engine - Koh, Yiyuan. (2012)
In the operation of a mini-jet engine, the turbine plays a critical role of driving the compressor. Without the turbine, the compressor will not turn and the engine cannot function. Thus, it is crucial that the turbine is properly designed to meet the power demand of the compressor.